The Influence of The Joyful Learning Model Assisted by Wordwall Type Open the Box on Mathematical Concept Understanding - Pebriani, Sarah Rizki; Karo-Karo S, Isran Rasyid (Desimal: Jurnal Matematika, 2026)
Despite the growing adoption of digital game-based learning in mathematics classrooms, empirical evidence explaining how technology-supported pedagogical models foster students’ mathematical conceptual understanding remains limited. This study investigated the effect of the Joyful Learning model assisted by the Wordwall Open the Box template on students’ mathematical conceptual understanding. A quasi-experimental pretest–posttest control group design was implemented at MAS Alwashliyah 22 Tembung, Indonesia, from 29 April to 19 May 2026. Eighty eleventh-grade students selected through purposive sampling were assigned to an experimental class (n = 40) and a control class (n = 40). Data were collected using an essay-based conceptual understanding test developed from 15 items, of which eight met the validity criteria, with a reliability coefficient of 0.7951. Data analysis included the Liliefors normality test, the F-test for homogeneity, and an independent-samples t-test. The experimental class improved from a mean pretest score of 46.975 to 86.525, whereas the control class increased from 47.150 to 57.525, with respective mean gains of 39.550 and 10.375. The difference between the two groups was statistically significant (t = 18.038), indicating that students experiencing Joyful Learning supported by Wordwall achieved substantially stronger conceptual development than those receiving conventional instruction. These findings suggest that the educational value of digital game-based learning lies not in technological novelty itself but in its pedagogically structured integration with active participation, collaborative knowledge construction, and formative feedback. This study contributes to the literature by providing empirical evidence that constructivist pedagogy and purposeful technology integration operate synergistically to promote meaningful mathematical conceptual understanding.